2005
DOI: 10.1186/1472-6890-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Tissue eosinophilia: a morphologic marker for assessing stromal invasion in laryngeal squamous neoplasms

Abstract: Background: The assessment of tumor invasion of underlying benign stroma in neoplastic squamous proliferation of the larynx may pose a diagnostic challenge, particularly in small biopsy specimens that are frequently tangentially sectioned. We studied whether thresholds of an eosinophilic response to laryngeal squamous neoplasms provides an adjunctive histologic criterion for determining the presence of invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 14 publications
(10 reference statements)
2
41
1
1
Order By: Relevance
“…The mechanisms underlying eosinophilic accumulation in invasive SCC are not fully known [9]. It was suggested that lesion-derived eosinophil chemotactic factors induce eosinophilic infiltration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms underlying eosinophilic accumulation in invasive SCC are not fully known [9]. It was suggested that lesion-derived eosinophil chemotactic factors induce eosinophilic infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Agarwal et al [8] reported findings similar to those of Spiegel et al and suggested that the presence of stromal eosinophils should result in a search for invasion in deeper sections in lesions of cervical intraepithelial neoplasia II and III Alrawi et al [2] reported higher eosinophilic counts in laryngeal SCC lesions than in SCCIS, concluding that tissue eosinophilia might be a pathological feature associated with stromal invasion. Similarly, Said et al [9] reported that an elevated eosinophil count in squamous neoplasia of the larynx is associated with stromal invasion, and recommended a thorough search for invasion when the number of infiltrating eosinophils is > 10 eosinophils HPF-1 and/or 20 eosinophils 10 HPFs-1. More recently, Jain et al [1] observed higher eosinophil counts in oral SCC than those in oral dysplasia, suggesting they play a role in stromal invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltrados de eosinófilos foram observados anteriormente em CCEs do TAS de bovinos intoxicados por samambaia (Polack 1990), porém sua presença não foi discutida. Eosinófilos têm sido constantemente observados em CCEs de laringe em humanos (Ercan et al 2005, Said et al 2005) e foram correlacionados com um maior potencial de invasão tumoral (Said et al 2005) ou com a idade dos pacientes, sendo mais freqüentes em pessoas acima de 60 anos (Ercan et al 2005). O papel dos eosinófilos nos CCEs de bovinos intoxicados por samambaia não está definido e poderá vir a ser investigado.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Recently, eosinophilia has been investigated in head and neck carcinomas, especially the oral cavity carcinomas [7][8][9][10][11]. Although it has been shown that the relationship between eosinophil count and prognosis is statistically significant, it still remains controversial [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%